Wall-resolved large-eddy simulation of turbulent channel flows with rough walls. Issue 1 (January 2021) - Li, Shilong; Yang, Xiaolei; Jin, Guodong; He, Guowei
Highlights: Turbulent flow over rough wall is simulated via wall-resolved large-eddy simulation. Rough elements are represented using the curvilinear immersed boundary method. Present results are compared with those from the volume of fluid method. Abstract: Turbulent flows over rough surfaces widely exist in nature and industry. Investigating its mechanism is of theoretical and practical significance. In this work we simulate the turbulent channel flow with rough walls using large-eddy simulation with rough elements resolved using the curvilinear immersed boundary method and compare the results obtained in this work with those in the paper by Yuan and Piomelli ( J. Fluid Mech., vol. 760, pp. R1, 2014), where the volume of fluid method was employed for modeling rough elements. The mean streamwise velocity profiles predicted by the two methods agree well with each other. Differences in Reynolds stresses and dispersive stresses are observed, which are attributed to the different approaches in dealing with the complex geometry of the rough surface.